Colloidal stability and ecotoxicity of multiwalled carbon nanotubes: Influence of select organic matters. (9th November 2015) - Cerrillo, Cristina; Barandika, Gotzone; Igartua, Amaya; Areitioaurtena, Olatz; Uranga, Nerea; Mendoza, Gemma
Abstract: In the last few years, the release of multiwalled carbon nanotubes (MWCNTs) into the environment has raised serious concerns regarding their fate and potential impacts. Aquatic organisms constitute an important pathway for their entrance and transfer throughout the food web, and the current demand for standardization of methodologies to analyze the interactions of MWCNTs with them requires aquatic media that represent natural systems. However, the inherent hydrophobicity of MWCNTs and the substances present in natural waters may greatly affect their stability and bioavailability. The present study analyzes the influence of the most referenced synthetic and natural organic matters (Sigma‐Aldrich humic acid and Suwannee River natural organic matter) in the agglomeration kinetics and ecotoxicity of MWCNTs, with the aim of determining their suitability to fulfill the current standardization requirements. Natural organic matter provides increased colloidal stability to the MWCNTs' dispersions, which results in higher adverse effects on the key invertebrate organism Daphnia magna . Furthermore, the results obtained with this type of organic matter allow for observation of the important role of the outer diameter and content impurities of MWCNTs in their stability and ecotoxicity on daphnids. Sigma‐Aldrich humic acid appeared to alter the response of the organisms to carbon nanotubes compared with that observed in the presence of natural organic matter. Environ Toxicol Chem 2016;35:74–83. © 2015 SETAC